Biventricular circulatory support using single-device and dual-device configurations: Initial pump characterization in simulated heart failure model - Karimov, Jamshid H.; Miyagi, Chihiro; Flick, Christine R.; Polakowski, Anthony R.; Kuban, Barry D.; Kuroda, Taiyo; Horvath, Dennis W.; Fukamachi, Kiyotaka; Starling, Randall C. (Frontiers in Cardiovascular Medicine, 2023)
Objective Severe biventricular heart failure (BHF) can be remedied using a biventricular assist device (BVAD). Two devices are currently in development: a universal ventricular assist device (UVAD), which will be able to assist either the left, right, or both ventricles, and a continuous-flow total artificial heart (CFTAH), which replaces the entire heart. In this study, the in vitro hemodynamic performances of two UVADs are compared to a CFTAH acting as a BVAD. Methods For this experiment, a biventricular mock circulatory loop utilizes two pneumatic pumps (Abiomed AB5000™, Danvers, MA, USA), in conjunction with a dual-output driver, to create heart failure (HF) conditions (left, LHF; right, RHF; biventricular, BHF). Systolic BHF for four different situations were replicated. In each situation, CFTAH and UVAD devices were installed and operated at two distinct speeds, and cannulations for ventricular and atrial connections were evaluated. Results Both CFTAH and UVAD setups achieved our recommended hemodynamic criteria. The dual-UVAD arrangement yielded a better atrial balance to alleviate LHF and RHF. For moderate and severe BHF scenarios, CFTAH and dual UVADs both created excellent atrial pressure balance. Conversely, when CFTAH was atrial cannulated for LHF and RHF, the needed atrial pressure balance was not met. Conclusion Comprehensive in vitro testing of two different BVAD setups exhibited self-regulation and exceptional pump performance for both (single- and dual-device) BHF support scenarios. For treating moderate and severe BHF, UVAD and CFTAH both functioned well with respect to atrial pressure regulation and cardiac output. Though, the dual-UVAD setup yielded a better atrial pressure balance in all BHF testing scenarios.